Double-edged weapons: humor in The Fat Black Woman’s Poems and Lazy Thoughts of a Lazy Woman, by Grace Nichols - Galettini, Azucena (2020)
The second and third poetry collection (The Fat Black Woman’s Poems [1984] y Lazy Thoughts of a Lazy Woman [1989], respectively) by Grace Nichols, Guyanese author living in the United Kingdom since 1977, are related due to the use of humor. Criticized for utilizing this resource, seen as excess of lightness when addressing complex themes such as slavery, the harsh life of the Caribbean immigrant, or female sexuality, Nichols reclaims humor as a way of ascribing herself to Antillean tradition. In the current essay, we will explore through the analysis of four poems (two from each book) how humor operates in both collections and which simplifications it entails, emphasizing how the apparent lightness it gives is, seen as part of Caribbean tradition, another way of resistance.